Philosopher & Founder Rediscovery Of The Human Soul - - (Bridge Publications, 2012)
Rediscovery of the Human Soul is the story of Ron’s philosophic quest and his forging of the philosophy of Scientology. Various rare essays, selections and discussions from all critical junctures of his philosophic journey are included.